Retinal phototoxicity after macular hole surgery in a patient under paclitaxel - José M Ruiz-Moreno; María García‑Zamora; Jorge Ruiz‑Medrano (BMC Ophthalmology, 2023)
Abstract Background The purpose is to report the second case, to our knowledge, of suspected paclitaxel-induced phototoxic maculopathy following pars plana vitrectomy surgery. Case presentation 63-year-old phakic female who underwent an uneventful phaco-vitrectomy to treat a complete macular hole, developing macular phototoxicity in the post-operatively period that could not be explained by the surgery itself and could only be attributed to a possible photosensitization induced by the previous use of paclitaxel. Conclusions The use of paclitaxel has been widely extended as a chemotherapy drug to treat breast cancer. It works by altering the intracellular microtubular reorganization and, based on this mechanism of action, photosensitivity has been previously described. We report a case of suspected paclitaxel-induced macular phototoxicity following ocular endoillumination during vitrectomy surgery.